Pteridium spp. and Bovine Papillomavirus: Partners in Cancer - Medeiros-Fonseca, Beatriz; Abreu-Silva, Ana Lúcia; Medeiros, Rui; Oliveira, Paula A.; Gil da Costa, Rui M. (Frontiers in Veterinary Science, 2021)
Bovine papillomavirus (BPV) are a cause for global concern due to their wide distribution and the wide range of benign and malignant diseases they are able to induce. Those lesions include debilitating cutaneous and upper digestive papillomas, multiple histological types of urinary bladder cancer - most often associated with BPV1 and BPV2 - and squamous cell carcinomas of the upper digestive system, associated with BPV4. Clinical, epidemiological and experimental evidence shows that exposure to bracken fern (Pteridium spp.) and other related ferns plays an important role in allowing viral persistence and promoting the malignant transformation of early viral lesions. This carcinogenic potential has been attributed to bracken illudane glycoside compounds with immune suppressive and mutagenic properties, such as ptaquiloside. This review addresses the role of BPV in tumorigenesis and its interactions with bracken illudane glycosides. Current data indicates that inactivation of cytotoxic T lymphocytes and natural killer cells by bracken fern illudanes plays a significant role in allowing viral persistence and lesion progression, while BPV drives unchecked cell proliferation and allows the accumulation of genetic damage caused by chemical mutagens. Despite limited progress in controlling bracken infestation in pasturelands, bracken toxins remain a threat to animal health. The number of recognized BPV types has steadily increased over the years and now reaches 24 genotypes with different pathogenic properties. It remains essential to widen the available knowledge concerning BPV and its synergistic interactions with bracken chemical carcinogens, in order to achieve satisfactory control of the livestock losses they induce worldwide.